2023
DOI: 10.1002/smll.202206960
|View full text |Cite
|
Sign up to set email alerts
|

Covalently Grafted Biomimetic Matrix Reconstructs the Regenerative Microenvironment of the Porous Gradient Polycaprolactone Scaffold to Accelerate Bone Remodeling

Abstract: Integrating a biomimetic extracellular matrix to improve the microenvironment of 3D printing scaffolds is an emerging strategy for bone substitute design. Here, a “soft–hard” bone implant (BM‐g‐DPCL) consisting of a bioactive matrix chemically integrated on a polydopamine (PDA)‐coated porous gradient scaffold by polyphenol groups is constructed. The PDA‐coated “hard” scaffolds promoted Ca2+ chelation and mineral deposition; the “soft” bioactive matrix is beneficial to the migration, proliferation, and osteogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 54 publications
(62 reference statements)
1
16
0
Order By: Relevance
“…Our previous study proved that the introduction of polyphenols, such as DA, could induce angiogenesis and through the catechol-mediated Michael addition reaction and Ca 2+ chelation, HAD might operate as a macromolecular cross-linking agent to improve the integration of the nanointerface between Col I and nHAP. Since Ca 2+ plays a pivotal role in modulating osteoblastogenesis, Ca 2+ release characteristics of P 2 HCLS and P 3 HCLS were further analyzed.…”
Section: Resultssupporting
confidence: 59%
See 1 more Smart Citation
“…Our previous study proved that the introduction of polyphenols, such as DA, could induce angiogenesis and through the catechol-mediated Michael addition reaction and Ca 2+ chelation, HAD might operate as a macromolecular cross-linking agent to improve the integration of the nanointerface between Col I and nHAP. Since Ca 2+ plays a pivotal role in modulating osteoblastogenesis, Ca 2+ release characteristics of P 2 HCLS and P 3 HCLS were further analyzed.…”
Section: Resultssupporting
confidence: 59%
“…Though exogenous cells and growth factors are key regulators of each stage for accelerating bone healing, the unpredictable clinical risk has been constraining their transformation application . In the previous works, we demonstrated that endogenous stem cells (ESCs) were successfully recruited in situ to promote early osteogenesis and quick vascularization in cell/factor-free scaffolds with improved material designs, as well as integrating type I collagen (Col I) fibrillar matrices and hydroxyapatite (HAP) by the hybrid cross-linking mechanism mediated by dopamine-modified hyaluronic acid (HAD) . However, the closed pore walls and the long distance between pores in the scaffold generally restrict the cells’ migration.…”
Section: Introductionmentioning
confidence: 99%
“…This membrane can regenerate arc-shaped bone as well as dome-shaped calvarial bone . To cope with the structural and functional limitations of the PCL scaffolds failing to mimic the physiological microenvironment, Liu et al created a soft–hard bioactive construct by dopamine-mediated chemical integration, in which a biomimetic matrix was grafted onto a polydopamine-coated 3DP PCL scaffold (BM- g -DPCL) . The “hard” scaffolds promoted Ca 2+ chelation and mineral deposition, meanwhile the “soft” bioactive matrix is beneficial to the migration, proliferation, and osteogenic differentiation of stem cells in vitro, accelerated endogenous stem cell recruitment, and initiated rapid angiogenesis in vivo.…”
Section: Polymer Materialsmentioning
confidence: 99%
“…[3,4] Therefore, the fabrication of organic/inorganic interwoven hybrid scaffolds is expected to provide both mechanical support and biological activity for complex large irregular bone defects (e.g., cranial trauma). [5][6][7][8] Polyvinyl alcohol (PVA) is a highly plastic and water-soluble polymer often used as a filler excipient for interventional catheter products, orthopedic surgical products, or basic research on artificial cartilage materials. [9][10][11][12] It has good toughness and processability that allow efficient molding and secondary processing to precisely match the contours of irregular defective tissues, and it shows promising applications as a material for irregular craniomaxillofacial defects.…”
Section: Introductionmentioning
confidence: 99%
“…Our preliminary study revealed that an organic bioactive fibrous matrix based on collagen I (Col I) and hyaluronic acid derivatives could promote the proliferation and diffusion of rabbit mesenchymal stem cells (rBMSCs) and enhance the enrichment and migration of rBMSCs in vitro through potential functional protein adsorption. [5,6,23,24] It may act as an effective protective layer of the prosthesis and a bioactive layer to promote stem cell recruitment and proliferation. Furthermore, utilizing the multi-reactivity of polyphenolic groups, the organic reactive fibrous matrix can be integrated better with mechanically supported prostheses, and the interweaving of the organic matrix into the inorganic prostheses has good potential structural and biological benefits.…”
Section: Introductionmentioning
confidence: 99%